Longitudinal Assessment of Diagnostic Test Performance Over the Course of Acute SARS-CoV-2 Infection. (30th June 2021) - Smith, Rebecca L; Gibson, Laura L; Martinez, Pamela P; Ke, Ruian; Mirza, Agha; Conte, Madison; Gallagher, Nicholas; Conte, Abigail; Wang, Leyi; Fredrickson, Richard; Edmonson, Darci C; Baughman, Melinda E; et al.
Abstract: Background: Serial screening is critical for restricting spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by facilitating timely identification of infected individuals to interrupt transmission. Variation in sensitivity of different diagnostic tests at different stages of infection has not been well documented. Methods: In a longitudinal study of 43 adults newly infected with SARS-CoV-2, all provided daily saliva and nasal swabs for quantitative reverse transcription polymerase chain reaction (RT-qPCR), Quidel SARS Sofia antigen fluorescent immunoassay (FIA), and live virus culture. Results: Both RT-qPCR and Quidel SARS Sofia antigen FIA peaked in sensitivity during the period in which live virus was detected in nasal swabs, but sensitivity of RT-qPCR tests rose more rapidly prior to this period. We also found that serial testing multiple times per week increases the sensitivity of antigen tests. Conclusions: RT-qPCR tests are more effective than antigen tests at identifying infected individuals prior to or early during the infectious period and thus for minimizing forward transmission (given timely results reporting). All tests showed >98% sensitivity for identifying infected individuals if used at least every 3 days. Daily screening using antigen tests can achieve approximately 90% sensitivity for identifying infected individuals while they are viral culture positive. Abstract : Adults newly infected with SARS-CoV-2 were sampled daily for saliva and nasal swab RT-qPCR, Quidel SARS Sofia antigen FIA, and viral culture. We compare test sensitivities at different stages of acute infection and as a function of testing frequency.